Development of a Heart Rate Monitoring System Using Arduino Technology - Kadhim, Mohammed Sattar Oudah; Mohsen, Hussein Mohsen Sahar; Mohammed, Hassanein Aziz Hashem; Ghali, Hussein Hakeem Abdulridha; Mohammed, Ali Hisham Haidar (American Journal of Botany and Bioengineering, 2025)
Monitoring heart rate is a vital aspect of personal and clinical healthcare, providing critical insights into an individual's cardiovascular status. With the increasing accessibility of open-source electronics, particularly the Arduino platform, it has become feasible to design cost-effective and portable heart rate monitoring systems. This research focuses on the development and implementation of a heart pulse detection system using an Arduino Uno. The sensor detects fluctuations in blood flow through the fingertip using infrared light, which is then converted into electrical signals processed by the microcontroller. The real-time pulse data is displayed using an LCD or OLED screen. This system was tested under different physical conditions, demonstrating reliable and accurate readings. The simplicity, affordability, and educational value of the system make it suitable for academic projects and personal health tracking. Furthermore, it lays the groundwork for more advanced wearable health monitoring devices in the future.